Converter-based Control using Co-Simulation with a Power System Simulation Tool - Raab, Alexander; Scheibe, Christian; Wellhoefer, Anatoli; Nguyen, Thi Thanh-Thuy; Frauenknecht, Dominik; Mehlmann, Gert (Conference on Sustainable Energy Supply and Energy Storage Systems, 2021)
The objective of this contribution is to implement a Co-simulation approach for control systems within RMS-based stability analyses of power systems. Inter-process communication via shared memory connects the specialized and focused software environments and enables the data exchange between them. A model of a point-to-point VSC-HVDC system with main controls is presented as the test system to be investigated. Simulations with the model in a fault case show that the results generated with the new approach are similar to those of a single-instance simulation with converted models. Simultaneously, in contrast to the existing alternatives the presented approach exhibits the benefits of Co-simulation related to efforts, costs, efficiency and model continuity, while the models remain within specialized best-in-class too
Keywords: Co-simulation; power system simulation; shared memory; VSC-HVDC